Pengaruh Penuaan Aspal Pada Karakteristik Campuran Beton Aspal Lapis Aus AC – WC - Mashuri, M.; Rahman, R. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2020)
The aging process of asphalt in the pavement layers of asphalt concrete road occurs when mixing in the Asphalt Mixing Plant and during the road service period. The asphalt aging process when mixing is called short-term aging and aging during the road service period is called long-term aging. AC - WC mixture is a wear layer and it is on the top layer of the surface which allows characteristics change that are influenced by several environmental factors (air, temperature and sunlight). This study aims to know the effect of asphalt aging on the characteristics of AC - WC mixture with Marshall method on some asphalt content that are 4.5%, 5.0%, 5.5%, 6.0%, 6, 5% and 7.0%. For testing on short-term aging (Short - Term Oven Aging, STOA) is by testing the mixture specimen AC - WC at 135o C before solidified for 4 hours and for long-term aging (Long - Term Oven Aging, LTOA) was carried out by testing the mixture specimen AC - WC at 85o C for 2 - 5 days. The results of this study found that asphalt aging had an effect on the characteristics of AC - WC mixture. Values of density, VFB, stability, flow tend to decrease with age. While VIM and VMA values tend to increase with age. Aging caused the mixture to became more rigid.